Canada and the Financing of the United Nations Emergency Force, 1957-1963 - Carroll, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2002)
AbstractThe current financial crisis of the United Nations is generally traced to the peacekeeping mission in the Congo and its price tag. This paper proposes that the roots of financial unrest lie rather as early as 1956, in the financing of the United Nations Emergency Force. Peacekeeping funding quickly became a litmus test of support for the United Nations - a sign of policy beyond platitudes. In Canada, the political popularity of peacekeeping required that the Diefenbaker government play an active role in trying to resolve the UN's financial predicament. However, despite the advantages that UNEF and peacekeeping brought to an unstable world, there was in fact little that Canada or the United Nations could do to force individual nations to financially support collective UN policies.